Pengaruh Kualitas SDM, Pemanfaatan Teknologi Informasi dan Sistem Pengendalian Internal terhadap Pengelolaan Keuangan Dana Desa Dengan Kecerdasan Spiritual Sebagai Variabel Moderasi - Soamole, Nur Nazma; Amin, Moh.; Malikah, Anik (e_Jurnal Ilmiah Riset Akuntansi, 2024)
The aim of this research is to analyze the influence of the quality of human resources (HR), information technology, and internal control systems on the financial management of village funds with spiritual intelligence as a moderating variable. The population in this study are village officials involved in financial management in their respective villages. The specified sample consisted of 126 respondents who met the criteria. The research method used was purposive sampling with a quantitative approach. This research uses primary data and moderated regression analysis (MRA). The research results show that:(1) the quality of human resources has a positive effect on the financial management of village funds. (2) the use of information technology has a positive effect on the financial management of village funds. (3) the internal control system has a positive effect on the financial management of village funds (4) spiritual intelligence strengthens the influence of the quality of human resources on the financial management of village funds (5) spiritual intelligence strengthens the influence of the use of information technology on the financial management of village funds. (6) spiritual intelligence is unable to strengthen the influence of the internal control system on the financial management of village funds.Keywords: Quality of human resources, information technology, internal control, financial management, spiritual intelligence